Volk, Jew and Devil: Ironic Inversion in Günter Grass's Dog Years - Lyle H. Smith Jr. (Studies in 20th & 21st Century Literature, 1978)
As Edward Diller pointed out in A Mythic Journey: Günter Grass's Tin Drum, the author of the Baltic Trilogy employs elements of myth and of the marvellous not only to give his stories local color, but also to establish patterns of symbolism. The present study maintains that Grass employs Baltic mythology and the language of mythopoesis throughout the whole of Dog Years as a means of parodying anti-Semitic myths embodied in Volkist race-ideology, thereby undercutting not only Nazism but also its cultural foundation. By identifying the novel's half-Jewish character, Eddi Amsel, with the gods of ancient Prussia, while simultaneously demonstrating his conformity with some of the standard traits claimed by Volkist anti-semitic propaganda to be uniquely and objectionably Jewish, Grass ironically inverts the traditional identification of land, Volk and life forces which formed the life and world view of most Germans from the early nineteenth century onward. The Jew, seen as «rootless» and alien by German anti-semites, becomes identified in Grass's novel with the values that Volkist ideologues held to be characteristic of the settled, rooted and «genuine» German. Simultaneously, Grass demonstrates in Amsel many of the characteristics advanced by the anti-semites as evidence of the Jew's inhuman and threatening character. The result–the eventual triumph of this arch-Germanic, arch-Jewish eiron in the midst of a hostile group of fascistic alazons–is a brilliant surprise. By appearing to substantiate anti-semitic doctrines in Eddi's case, Grass uncovers their absurdity by in fact examining that individual case very carefully, disclosing that Eddi is in closer and more intimate communion with his land and its cosmic creative forces–hence, more mystically and «genuinely» German-than are any of the book's major Gentile characters.
Keywords: Günter Grass; Dog Years; anti-semitism; irony; inversion; subversion; parody